Model Pembelajaran Berbasis Proyek terhadap Peningkatan Kemampuan Memecahkan Masalah Matematika Siswa SMP - Azis Azis; Asfin Herianto (Jurnal Akademik Pendidikan Matematika, 2021)
This study aims to determine the application of project-based learning models to improve the ability to solve math problems of class VIII students of SMP Negeri 14 Buton Tengah on cube and block material. This study was a type of experiental research. The population of this study were all students of VIII grade with a total of 42 students. The sampel in this study consisted of class VIII A as a control class of 20 students and class VIII B as an Experimental class of 22 students at SMP Negeri 14 Buton Tengah, even semester of the 2019/2020 school year. Data collection in this study was carried out using a research instrunent in the form of a test. The data obtained were then analyzed by descriptive analysis and inferential analysis and tested the hypothesis in the form t-test. The results obtained: (1) the average student learning outcomes in the experimental class pretest was 36,25; (2) the average student learning outcomes in the control class pretest was 35; (3) the average student learning outcomes in the final test of the experimental class were 85,25; (4) the average student learning outcomes in the final test of thecontrol class amounted to 48,41; (5) based on the results of hypothesis testing whit the t-test, the value of t-count = 7,795 and a significant value of r = 0,00. So that the application of the project-based learning model towards increasing the ability to solve math problems was no more effective than without applying the project-based learning model for VIII grade students of SMP Negeri 14 Buton Tengah on cube and block material.